2013
DOI: 10.1016/j.rvsc.2013.08.018
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rapid clearance of infectious bursal disease virus in peripheral blood mononuclear cells of chicken lines divergent for antibody response might be related to the enhanced expression of proinflammatory cytokines

Abstract: Infectious bursal disease (IBD) is an acute and highly contagious viral disease of young chickens caused by infectious bursal disease virus (IBDV). An effective way to control IBDV would be to breed chickens with a reduced susceptibility to IBDV infection. In the present work, we used chickens selected for high and low specific responses to sheep red blood cells (SRBC) (H and L, respectively) to assess the susceptibility of differential immune competent animals to IBDV infection. The peripheral blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…IFN-γ and IFN-β secreted by Th1 cells are involved in cell-mediated immune response (Zhang et al, 2014). Previous researches have also demonstrated that IFN-γ and IFN-β were involved in virus replication and antiviral response (Jain et al, 2013;Dar et al, 2014), present study showed that the expression of IFN-γ was increased in IBDVinfected chicks, and DG could inhibited the expression of IFN-γ.…”
Section: Discussionsupporting
confidence: 54%
“…IFN-γ and IFN-β secreted by Th1 cells are involved in cell-mediated immune response (Zhang et al, 2014). Previous researches have also demonstrated that IFN-γ and IFN-β were involved in virus replication and antiviral response (Jain et al, 2013;Dar et al, 2014), present study showed that the expression of IFN-γ was increased in IBDVinfected chicks, and DG could inhibited the expression of IFN-γ.…”
Section: Discussionsupporting
confidence: 54%
“…However, in the present study, we also observed a sustained upregulation of the genes expressing the immunosuppressive cytokines TGFb-1, 2 and 3, compared to mock controls (Figure 4). Previously, an upregulation of TGFb2 expression was observed in PBMCs of chickens infected with IBDV, which was linked to limiting inflammation mediated by Th1 cytokines (40), and another two studies reported an increase of TGF-b mRNA expression in the BF of IBDV infected birds (22, 41), and it has been associated with an induction of bursal tissue fibrosis in the late stage of infection (41). TGFb is produced or released by a range of immune cells, including T cells and monocytes/ macrophages (42).…”
Section: Discussionmentioning
confidence: 98%
“…F52/70 produced more clinical signs than 228E in older birds, yet CD4 + TGFb + and CD4 + CD25 + TGFb + cells infiltrated the BF at earlier time points in 228E infected birds, indicating their earlier numbers in the BF did not correlate with increased disease severity. Previously, an upregulation of TGFb2 expression was observed in PBMCs of chickens infected with IBDV, which was linked to limiting inflammation mediated by Th1 cytokines (40), so it is possible that early infiltration of these cells limits inflammation, although further studies are required to determine if this is the case. Moreover, F52/70 infection caused more immunosuppression in younger birds than older birds, and more immunosuppression than 228E in younger birds, however, the kinetics of CD4 + CD25 + TGFb + cell infiltration was the same between younger and older birds infected with F52/70, and the kinetics of CD4 + TGFb + and CD4 + CD25 + TGFb + cell infiltration was the same between F52/70 and 228E infection in younger birds, suggesting the infiltration of these cells into the BF is unlikely to be contributing to immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the degree of lesions and the amount of virus in the bursa may differ between breeds [ 24 , 45 , 46 ]. Dobner suggested that the presence of a higher viral load in the bursa corresponds to more severe microscopic lesions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%